ADIPOQ single nucleotide polymorphisms and breast cancer in northeastern Mexican women - Ricardo M. Cerda-Flores; Karen Paola Camarillo-Cárdenas; Gabriela Gutiérrez-Orozco; Mónica Patricia Villarreal-Vela; Raquel Garza-Guajardo; Marco Antonio Ponce-Camacho; Ana Lilia Castruita-Ávila; Juan Francisco González-Guerrero; Iram Pablo Rodríguez-Sánchez; Ana Laura Calderón-Garcidueñas; Hazyadee Frecia Rodríguez-Gutierrez; Juan Carlos Arellano-Barrientos; et al. (BMC, 2020)
Abstract Background Adiponectin gene (ADIPOQ) polymorphisms have been shown to affect adiponectin serum concentration and some have been associated with breast cancer (BC) risk. The aims of this study were to describe the frequency of single nucleotide polymorphisms (SNPs) of ADIPOQ in Mexican women with BC and to determine if they show an association with it. Methods DNA samples from 397 patients and 355 controls were tested for the ADIPOQ gene SNPs: rs2241766 (GT) and rs1501299 (GT) by TaqMan allelic discrimination assay. Hardy-Weinberg equilibrium (HWE) was tested. Multiple SNP inheritance models adjusted by age and body mass index (BMI) were examined for the SNP rs1501299. Results We found that in the frequency analysis of rs1501299 without adjusting the BMI and age, the genotype distribution had a statistically significant difference (P = 0.003). The T allele was associated with a BC risk (OR, 1.99; 95% CI 1.13-3.51, TT vs. GG; OR, 1.53; 95% CI 1.12-2.09, GT vs. GG). The SNP rs2241766 was in HW disequilibrium in controls. In conclusion, the rs1501299 polymorphism is associated with a BC risk. Conclusions Identification of the genotype of these polymorphisms in patients with BC can contribute to integrate the risk profile in both patients and their relatives as part of a comprehensive approach and increasingly more personalized medicine.